Sawing mud superfine silicon powder sorting method based on step screening and functional application thereof

CN122977733APending Publication Date: 2026-10-27SEDIN ENG CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611055547.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]针对现有锯泥资源化利用技术中产品附加值低、未实现按粒径梯级分离及分级表面改性以匹配不同功能填料应用场景的缺陷问题,本发明提供了一种基于梯级筛分的锯泥超细硅微粉分选方法及其功能化应用

Benefits of technology

[0035]1、首次提出锯泥“梯级分离+分级改性+功能化应用”三位一体的技术方案,实现锯泥100%全量化的高值化梯级利用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977733A_ABST
    Figure CN122977733A_ABST
Patent Text Reader

Abstract

The application discloses a sawing mud superfine silicon powder sorting method based on step screening and functional application thereof and belongs to the technical field of solid waste resource utilization. In view of the defects of low product added value, non-implementation of step separation according to particle size and non-implementation of step surface modification to match different functional filler application scenarios in the existing sawing mud resource utilization technology, the application obtains coarse, medium and superfine three-stage powders through step screening after pretreatment of the sawing mud, and the superfine powders are subjected to airflow classification to obtain silicon micro powder with D50 of 5 microns. According to the specific surface area and surface activity difference of each particle size component, step surface modification is carried out on the components by using stearic acid, titanate and silane coupling agent. The modified coarse particle level is used as an increment filler, the medium particle level is used as a body quality filler, and the superfine powder is used as a reinforcing filler, so that 100% full utilization of the sawing mud is realized. The application is a physical method and is free of pollution. After the modified superfine powder is filled into PP, the bending modulus is increased by 20% to 40%, and the added value of the solid waste is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste resource utilization technology, specifically involving a method for sorting ultrafine silica powder from sawdust based on cascade screening and its functional applications. Background Technology

[0002] Sawdust is a large-scale solid waste generated by the stone processing industry (mainly granite and marble cutting and polishing). Industry estimates suggest that my country produces over ten million tons annually, with a stockpile reaching hundreds of billions of tons. Such a massive stockpile, if left unchecked for a long period, will continuously exacerbate land occupation, water pollution, and ecological risks. The main chemical components of sawdust are SiO2 (typically 65%–75%) and Al2O3 (10%–18%), and it also contains K2O, Na2O, CaO, MgO, etc. This high-silicon, high-alumina composition gives it the potential to be used as an inorganic functional filler.

[0003] Existing sawdust resource utilization technologies are mostly concentrated in the building materials field, such as as concrete admixtures, or in the production of expanded clay or blocks. These applications typically have low added value. Regarding the high-value utilization of sawdust, a patent has disclosed a method for separating ultrafine silica powder from sawdust using fluidized bed technology (CN104386701A). However, this method only involves the separation of a single particle size fraction and does not perform surface modification or functionalization treatment on the separated products, limiting its application scope and economic value. Another patent discloses a comprehensive utilization method for sawdust tailings containing iron, feldspar, quartz, and other granite-type slabs (CN112844814A). Its technical solution includes steps such as grading, grinding, and magnetic separation, primarily aimed at recovering iron and feldspar concentrates, but does not involve surface modification treatment of sawdust powder as a functional filler. Furthermore, although some studies have reported using sawdust to replace traditional calcium carbonate as a filler in resin matrices, a systematic integrated technical solution of "tiered separation—gradation modification—functionalization application" has not yet been formed.

[0004] Sawdust powders of different particle sizes exhibit significant differences in specific surface area, surface activity, agglomeration tendency, and compatibility with different matrix resins. However, current technologies have not fully recognized the value of these differences, nor have they developed differentiated surface modification strategies and matching application scenarios for different particle sizes. Coarse-grained powders have small specific surface area and low surface activity, but good flowability, making them suitable as extender fillers. Ultrafine powders have large specific surface area and high surface activity, but are prone to agglomeration, requiring targeted modification to exert a reinforcing effect. Medium-grained powders fall between the two and are suitable as extender fillers. Summary of the Invention

[0005] To address the shortcomings of existing sawdust resource utilization technologies, such as low product added value and failure to achieve particle size-based tiered separation and graded surface modification to match different functional filler application scenarios, this invention provides a sawdust ultrafine silica powder sorting method based on tiered sieving and its functional applications.

[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0007] A method for separating ultrafine silica powder from sawdust based on stepped sieving includes the following steps:

[0008] (1) Pretreatment

[0009] Raw sawdust from stone processing is dehydrated by pressure filtration, sun-drying, or low-temperature drying to control the moisture content to ≤15%, resulting in dehydrated sawdust. This dehydrated sawdust is then crushed and ground to obtain a specific surface area ≥300 m². 2 / kg of sawdust powder.

[0010] (2) Cascade screening and sorting

[0011] The pretreated sawdust powder was sequentially sieved through standard sieves of 60-80 mesh, 160-200 mesh, and 325-400 mesh to obtain:

[0012] Coarse particle size: material passing through an 80-mesh sieve, particle size ≥180μm;

[0013] Medium particle size fraction: material under 200 mesh sieve and material over 80 mesh sieve, with a particle size between 75 and 180 μm;

[0014] Ultrafine primary powder composition: material passing through a 325-mesh sieve, particle size ≤45μm.

[0015] Actual testing revealed significant differences in chemical composition, mineral composition, whiteness, specific surface area, and impurity content among the particle size fractions obtained from the graded sieving. The coarse-grained fraction (≥180μm) exhibited a relatively high SiO2 content (72%–74% measured), an Al2O3 content of approximately 12%–13%, a whiteness of approximately 58%–62%, and a specific surface area typically <1m². 2 / g; the medium-sized component (75~180μm) has a SiO2 content of approximately 69%~71%, an Al2O3 content of approximately 13%~14%, a whiteness of approximately 63%~67%, and a specific surface area of ​​approximately 1~3m2 / g; the ultrafine primary powder (≤45μm) has a SiO2 content of approximately 67%~69%, an Al2O3 content of approximately 14%~16%, a whiteness of approximately 70%~74%, and a specific surface area of ​​up to 5~20m2 / g. 2 / g. The above differences arise because minerals such as quartz, feldspar, and mica in granite sawdust have different hardnesses (quartz Mohs hardness 7, feldspar 6-6.5, mica 2.5-3) and dissociation characteristics. During grinding, quartz particles, which are hard and tough, are not easily ground and tend to accumulate in the coarse-grained stage, resulting in a higher SiO2 content and lower Al2O3 content in the coarse-grained stage. Conversely, relatively easily ground minerals such as feldspar and mica tend to accumulate in the fine-grained stage, leading to an increase in Al2O3 content and a relative decrease in SiO2 content. Smaller particle size results in a larger specific surface area and higher surface energy. At the same time, the quartz content is relatively lower and the feldspar content is increased in the fine-grained stage, and iron impurities are further dissociated and dispersed during fine grinding, resulting in improved whiteness. The significant differences in chemical composition, specific surface area, and whiteness among the above particle sizes constitute the material basis for graded utilization.

[0016] The ultrafine primary powder is fed into an air classifier for secondary classification, with the classifier wheel speed controlled at 2000~4000 rpm and the induced draft fan air volume at 500~1500 m³ / h. 3 / h, to obtain ultrafine silica powder product with D90≤20 μm and D50≤5 μm, with a whiteness ≥70%.

[0017] Compared to ultrafine primary powders, finished ultrafine silica powder has a narrower particle size distribution and a finer median particle size (D50≤5 μm). The narrower particle size distribution means that the particle size is more uniform, and when used as a filler, it is more evenly dispersed in the matrix, reducing stress concentration points caused by large particles. The ultrafine particles with D50≤5μm have a significantly increased specific surface area and higher surface activity. After surface modification, the interfacial bonding force with the matrix resin is stronger, and the reinforcing effect is far superior to the product that has only been screened.

[0018] Optionally, a magnetic separation unit can be set up during the cascade screening process to remove ferromagnetic impurities from the sawdust and improve the whiteness of the ultrafine powder.

[0019] (3) Graded surface modification treatment

[0020] Take coarse-grained components, medium-grained components, and ultrafine silica powder products after air-separation, and mix them separately with a surface modifier at a mass ratio of 100:0.5~3. Activate the mixture by high-speed stirring at 60℃~120℃ for 10~30 minutes to ensure the surface modifier fully coats the surface of sawdust particles of different sizes. The surface modifier is selected from one or more of silane coupling agents, titanate coupling agents, stearic acid, or stearate.

[0021] Because the specific surface area and surface active site density of different particle size components vary significantly, the required adsorption capacity and type of adsorbent also differ. Specifically:

[0022] Coarse-grained components (≥180μm) have the smallest specific surface area and low density of surface active sites. They are mainly used as additive fillers to reduce costs and improve processing flowability. Lower-cost stearic acid or stearates are preferred for surface coating modification, primarily to improve particle surface polarity and enhance initial compatibility with the matrix. The modifier ratio should be 100:0.5~1. Stearic acid-modified coarse-grained components are superior to silane coupling agents in reducing system viscosity, and are also more cost-effective, offering a significant cost-performance advantage.

[0023] Medium-sized particles (75~180μm) have a moderate specific surface area and a low oil absorption value. Titanate coupling agents are suitable for modification. These modifiers have good adaptability to powders with high water content and can form a monolayer coating on the particle surface, effectively improving the compatibility of powders with coatings and adhesives. The modifier dosage should be 100:1~2.

[0024] Ultrafine powders (D50≤5μm) have a large specific surface area and high surface energy, and their surface is rich in silanol active sites. Therefore, silane coupling agents (such as KH-550 and KH-570) are suitable as modifiers. These agents can form strong chemical bonds with the particle surface through siloxane bonds (Si—O—Si) and also have good affinity in the organic matrix, thus achieving chemically bonded interfacial bonding. The modifier dosage should be 100:2~3. If the dosage is insufficient, a large number of uncovered polar regions will remain on the particle surface, which are prone to agglomeration due to van der Waals forces and electrostatic forces. If the dosage is excessive, multiple physical adsorption layers will form on the particle surface, which is detrimental to chemical bonding with the matrix and reduces the reinforcing effect. To improve modification efficiency and dispersibility, a dispersant of 0.1%~0.5% of the powder mass can be added during the modification process, selected from one or more of polyethylene glycol, sodium hexametaphosphate, or sodium tripolyphosphate.

[0025] (4) Functional compounding and application

[0026] Depending on the target application area, the modified functional filler obtained after graded surface modification treatment can be compounded and mixed with functional additives at a mass ratio of 100:0.2~2. The functional additives are selected from one or more of antioxidants, light stabilizers, flame retardants, and antistatic agents to obtain the finished functional filler.

[0027] The functional applications of different particle size components after graded surface modification are closely related to their particle size characteristics and surface properties:

[0028] After modification with stearic acid or stearate, the surface polarity of coarse-grained components (particle size ≥ 180 μm) is reduced, resulting in a smaller increase in viscosity of the filled system and good processing fluidity. This makes them suitable as incremental fillers in plastic and rubber products, primarily serving to reduce costs and improve processing fluidity. However, due to their small specific surface area and limited interfacial bonding area with the matrix, their contribution to mechanical property reinforcement is relatively low, making them unsuitable for applications requiring high strength.

[0029] The medium-sized component (particle size 75~180μm), after modification with a titanate coupling agent, exhibits good compatibility with coatings and adhesives, making it suitable for extender fillers. Its particle size matches typical coating thicknesses (approximately 50~150μm), and appropriate filling can form a dense particle packing structure in the coating film, helping to regulate system viscosity and improve coating hiding power and abrasion resistance.

[0030] After modification with a silane coupling agent, the ultrafine powder component (D50≤5μm, D90≤20μm, whiteness≥70%) forms a chemically bonded organic coating layer on the particle surface, resulting in high interfacial bonding strength with the polymer matrix. This component is suitable as a reinforcing filler for high-performance plastics and functional coatings. When added to PP at a loading of 15%~20%, the flexural modulus of the composite material increases by 20%~40% compared to pure PP, the tensile strength retention rate is ≥95%, and the surface quality of the product is significantly improved. If only sieved through a 325-mesh sieve without further air classification (D90≤45μm), the reinforcing effect is significantly lower than that of ultrafine powder with air classification due to the coarser particle size and wider distribution. It is only suitable for low- to mid-range filler applications where particle size requirements are less stringent.

[0031] If different particle size components are applied cross-referenced in mismatched scenarios, performance deteriorates: using ultrafine powder in incremental filler scenarios corresponding to coarse particles can improve the reinforcing effect to some extent, but it significantly increases the system viscosity and processing difficulty, leading to a substantial increase in cost while the performance gain is limited, resulting in a reduced cost-effectiveness; using coarse particles in reinforcing scenarios corresponding to ultrafine powders results in a significant decrease in tensile strength and flexural modulus of the composite material due to the excessively large particle size, small specific surface area, and weak interfacial bonding, which prevents effective stress transfer and dispersion. The above comparison further verifies the technical rationale for matching each particle size component to its corresponding application scenario according to its particle size characteristics. Preferred technical solution: The sawdust is granite sawdust with a SiO2 content ≥65% and an Al2O3 content ≥10%.

[0032] Preferred technical solution: During the sawdust pretreatment process, add a grinding aid (selected from one or more of triethanolamine, ethylene glycol, and sodium polyacrylate) at a mass of 0.1% to 0.5% of the sawdust mass to improve grinding efficiency.

[0033] The common technical features of this invention and the prior art are that they both involve grinding and sieving and grading sawdust.

[0034] Compared with the prior art, the present invention has the following advantages:

[0035] 1. For the first time, a three-in-one technical solution of "tiered separation + graded modification + functional application" for sawdust was proposed, realizing 100% full-scale high-value tiered utilization of sawdust.

[0036] 2. The entire process is a physical method, without the addition of acid or alkali chemical raw materials, and does not generate wastewater or exhaust gas pollution, making it environmentally friendly.

[0037] 3. Graded modification allows for more precise dosage of modifiers for each particle size component, significantly increasing the added value of the product.

[0038] 4. Using sawdust as raw material to prepare ultrafine silica micropowder functional fillers significantly reduces production costs. Attached Figure Description

[0039] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0040] Figure 1 This is a schematic diagram of the process flow of the present invention. Detailed Implementation

[0041] To gain a deeper understanding of this invention, we will provide a comprehensive and detailed description. However, this invention has various implementations and is not limited to the specific examples listed herein. These examples are presented to enhance a full understanding of the disclosure of this invention.

[0042] Example 1 (Taking a granite sawdust from Shandong as an example)

[0043] (1) Raw materials: granite sawdust (after pressure filtration, dehydration and drying) produced by a stone processing plant in Shandong Province was taken. It was grayish-white powder with a measured moisture content of 15.3%. The main components on a dry basis were: SiO2 70.2%, Al2O3 13.5%, Fe2O3 1.3%, CaO 1.8%, MgO 0.9%, K2O 4.2%, Na2O 3.1%, and loss on ignition 4.2%.

[0044] (2) Pretreatment: The sawdust was ground in a planetary ball mill (ball-to-material ratio 8:1, rotation speed 300 rpm, grinding time 35 minutes). The specific surface area of ​​the output powder was measured to be 362 m². 2 / kg, with a median particle size D50 of 22.5 μm.

[0045] (3) Stepwise sieving: The ground powder was passed through 60-mesh, 200-mesh, and 325-mesh standard sieves in sequence. The mass of the material on each sieve and the material under each sieve were weighed. The yields were: coarse particles (≥250 μm) 22.3%, medium particles (75~250 μm) 47.6%, and ultrafine primary powder (≤45 μm) 30.1%. The ultrafine primary powder was fed into an air classifier (classifier wheel speed 2800 rpm, induced draft fan air volume 1000 m³ / h). 3 (h) to obtain ultrafine silica powder product with D50=3.8 μm, D90=15.2 μm, and whiteness 78.5% (if magnetic separation is added to remove iron, the whiteness can be increased to more than 83%).

[0046] (4) Surface modification: Take ultrafine silicon powder and add silane coupling agent KH-550 at a mass ratio of 100:1.2. Stir and activate at 100°C for 20 minutes in a high-speed mixer to obtain modified ultrafine silicon powder.

[0047] (5) Functional compounding: Modified ultrafine silica powder and antioxidant 1010 were compounded at a ratio of 100:0.5 and used for PP plastic filling modification. The PP was added at a filling amount of 15% to 20%, and after twin-screw extrusion granulation, it was injection molded. The test results showed that the tensile strength of the composite material was improved or maintained well compared with pure PP, and the flexural modulus was significantly increased.

[0048] Example 2 (Taking a granite sawdust from Sichuan as an example)

[0049] (1) Raw materials: granite sawdust produced by a stone processing plant in Sichuan Province was used. It was light gray in appearance and had a slurry-like consistency. The measured moisture content was 70.2%. The main components by mass fraction were: SiO2 66.8%, Al2O3 15.2%, Fe2O3 1.9%, CaO 1.5%, MgO 0.7%, K2O 4.0%, Na2O 2.8%, and loss on ignition 5.1%.

[0050] (2) Pretreatment: The sawdust was dewatered to a moisture content of 24.5% by plate and frame filter press, and then naturally dried for 2 days to a moisture content of 8.2%. It was then ground in a planetary ball mill (ball-to-material ratio 8:1, speed 300 rpm, grinding time 40 minutes, due to the slightly high hardness of the raw material). The specific surface area of ​​the output powder was measured to be 345 m². 2 / kg, with a median particle size D50 of 24.0 μm.

[0051] (3) Scale sieving and air classification: A combination of 70 mesh, 180 mesh, and 350 mesh standard sieves was used. The mass of the material on and under each sieve was weighed, and the yields were: coarse particles (≥212 μm) 20.8%, medium particles (88~212 μm) 49.5%, and ultrafine primary powder (≤43 μm) 29.7%. The ultrafine primary powder was fed into an air classifier (classifying wheel speed 3000 rpm, induced draft fan air volume 1100 m³ / h). 3 ( / h) to obtain ultrafine silica powder product with D50=4.2 μm, D90=17.5 μm, and whiteness of 74.2% (which can be increased to over 80% after magnetic separation to remove iron).

[0052] (4) Surface modification: Take ultrafine silicon powder and add silane coupling agent KH-550 at a mass ratio of 100:1.5 (due to the slightly high iron content, the amount of coupling agent is increased by 0.3 kg to improve dispersion). Stir and activate at 100°C for 25 minutes in a high-speed mixer to obtain modified ultrafine silicon powder.

[0053] (5) Functional compounding: Modified ultrafine silica powder, antioxidant 1076, and stearic acid were compounded in a ratio of 100:0.4:0.3 to obtain a composite filler. This filler was added to PVC at a loading of 20%, along with calcium-zinc stabilizer and lubricant. The mixture was then subjected to open milling and hot pressing. The results showed that the composite material had good processing fluidity, a smooth surface, and mechanical properties that met general usage requirements.

[0054] Comparative Example

[0055] To demonstrate that the technical solution of this application produces a technical effect that differs from the prior art, the following comparative examples are set up:

[0056] Comparative Example 1 (Non-tiered screening scheme)

[0057] The sawdust powder ground in Example 1 was directly surface modified without cascade sieving (using the same modification conditions as the ultrafine component in Example 1: KH-550, 100:1.2, activation at 100℃ for 20 minutes). Then, it was added to the PP matrix at a 20% filler content, granulated by twin-screw extrusion, and injection molded to test its mechanical properties.

[0058] Comparative Example 2 (Unmodified Solution)

[0059] The powders obtained in Example 1 were mixed according to the original yield ratios after gradation sieving (22.3% coarse particles, 47.6% medium particles, and 30.1% ultrafine powder) without surface modification treatment. The mixture was then directly added to the PP matrix at a filler content of 20%, granulated by twin-screw extrusion, and injection molded. The mechanical properties were then tested.

[0060] Comparative Example 3 (Single ultrafine powder utilization scheme, referring to the idea of ​​CN104386701A)

[0061] Only the ultrafine silica powder (D50=3.8μm) obtained by air-flow classification in Example 1 was surface modified with KH-550 at a ratio of 100:1.2 and added to the PP matrix at a filling amount of 20%. The coarse and medium particle size components were not utilized, and its mechanical properties were tested.

[0062] Comparative Example 4 (Uniform Modification Scheme)

[0063] The powders obtained in Example 1 were mixed according to the original yield ratios after gradation sieving (22.3% coarse powder, 47.6% medium powder, and 30.1% ultrafine powder). They were then uniformly modified under the same modification conditions as the ultrafine component in Example 1 (KH-550, 100:1.2, activation at 100°C for 20 minutes). The mixture was then added to the PP matrix at a 20% filler content, granulated by twin-screw extrusion, and injection molded. Its mechanical properties were then tested.

[0064] Table 1 Performance Test Results

[0065]

[0066] From the table above, we can see that:

[0067] (1) Comparison of Example 1 and Comparative Example 3 (single ultrafine powder scheme): The tensile strength, flexural modulus and impact strength of the two are basically the same, indicating that the modification effect of the present invention on ultrafine powder has reached the same level as the prior art. However, the coarse and medium particle size components (accounting for about 70% in total) in Comparative Example 3 were not utilized, while the present invention achieves 100% full utilization of sawdust, and the comprehensive economic benefits are significantly better than those of Comparative Example 3.

[0068] (2) Comparison of Example 1 and Comparative Example 4 (uniform modification scheme): The tensile strength (33.8 MPa) of Example 1 is much higher than that of Comparative Example 4 (29.2 MPa), the flexural modulus (1820 MPa) is much higher than that of Comparative Example 4 (1560 MPa), and the impact strength (3.9 kJ / m) is much higher. 2 The value was higher than that of Comparative Example 4 (3.0 kJ / m). 2 This is because the specific surface area of ​​coarse-grained and ultrafine powders differs significantly (<1m²). 2 / g vs 5~20m 2 / g), the amount of modifier used in the uniform modification was excessive for coarse particles (waste) and insufficient for ultrafine powders (insufficient coating), resulting in the overall mechanical properties being far lower than those of Example 1 with graded optimization modification, which proves the superiority of the graded modification strategy.

[0069] (3) Comparison of Example 1 and Comparative Example 1 (without cascade screening scheme): The tensile strength (28.6 MPa) and impact strength (2.8 kJ / m) of Comparative Example 1 are significantly higher. 2 The results were significantly lower than those of Example 1. This is because the coarse particles formed stress concentration points in the matrix before sieving, which easily led to crack propagation under external force. At the same time, the melt flow index (7.8 g / 10 min) was significantly higher than that of Example 1 (6.2 g / 10 min), indicating that the inclusion of coarse particles actually increased the fluidity of the system (weak interfacial bonding between the filler and the matrix), which proves that the ultrafine powder formed a strong interfacial bond with the matrix after good modification.

[0070] (4) Comparison of Example 1 and Comparative Example 2 (unmodified): The mechanical properties of Comparative Example 2 are significantly lower than those of Example 1, especially the tensile strength (25.3 MPa) and impact strength (2.9 kJ / m). 2 This demonstrates that unmodified sawdust powder has weak interfacial bonding with the PP matrix, making it unable to effectively transfer and disperse stress. Surface modification is a necessary prerequisite for achieving functional applications.

[0071] (5) Comparison of Example 1 with pure PP: The flexural modulus (1820MPa) of Example 1 is about 35% higher than that of pure PP (1350MPa), and the tensile strength retention rate is ≥95% (32.5MPa→33.8MPa), achieving a good balance between rigidity and toughness, proving that the modified ultrafine silica powder plays a good reinforcing role in PP.

[0072] Contents not described in detail in this specification are prior art known to those skilled in the art. Although illustrative specific embodiments of the invention have been described above to facilitate understanding by those skilled in the art, it should be understood that the invention is not limited to the scope of the specific embodiments. Various modifications are readily apparent to those skilled in the art as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims, and all inventions utilizing the concept of this invention are protected.

Claims

1. A method for separating ultrafine silica powder from sawdust based on stepped sieving, characterized in that, Includes the following steps, (1) Pretreatment: The raw sawdust produced by stone processing is dehydrated to a moisture content of ≤15%, and then crushed and ground to obtain sawdust powder; (2) Step-by-step screening and sorting: The pretreated sawdust powder is sequentially screened through a standard sieve to obtain coarse-grained components, medium-grained components and ultrafine primary powder components respectively; the ultrafine primary powder is sent to an air classifier for secondary classification to obtain ultrafine silica powder finished product. (3) Graded surface modification treatment: Take the coarse-grained component, medium-grained component and ultrafine silica powder finished product respectively, and mix them with surface modifiers for surface modification treatment; wherein, the types and / or amounts of surface modifiers used for coarse-grained component, medium-grained component and ultrafine silica powder finished product are different. (4) Functional compounding and application: The modified functional fillers obtained after graded surface modification are applied to different functional application scenarios according to the particle size level.

2. The method according to claim 1, characterized in that, In step (2), the tiered sieving is carried out by using standard sieves of 60-80 mesh, 160-200 mesh, and 325-400 mesh in sequence, respectively to obtain: coarse particles are the material on the 80 mesh sieve, medium particles are the material under the 200 mesh sieve and the material on the 80 mesh sieve, and ultrafine primary powder is the material under the 325 mesh sieve.

3. The method according to claim 1, characterized in that, In step (2), the speed of the stager wheel in the airflow grading process is 2000~4000 rpm, and the air volume of the induced draft fan is 500~1500 m³ / h. 3 / h, the resulting ultrafine silica powder product has D90≤20 μm and D50≤5μm.

4. The method according to claim 1, characterized in that, In step (2), a magnetic separation iron removal unit is set up during the cascade screening process.

5. The method according to claim 1, characterized in that, The surface modifier mentioned in step (3) is selected from one or more of silane coupling agents, titanate coupling agents, stearic acid or stearate; the surface modification treatment conditions are: the mass ratio of sawdust powder to surface modifier is 100:0.5~3, and the mixture is stirred and activated at 60℃~120℃ for 10~30 minutes.

6. The method according to claim 5, characterized in that: The coarse-grained component is surface-modified with stearic acid or stearate, and the mass ratio of sawdust powder to surface modifier is 100:0.5~1; the medium-grained component is surface-modified with titanate coupling agent, and the mass ratio of sawdust powder to surface modifier is 100:1~2; the ultrafine silica powder product is surface-modified with silane coupling agent, and the mass ratio of sawdust powder to surface modifier is 100:2~3.

7. The method according to claim 1, characterized in that, In step (3), during the surface modification process, a dispersant of 0.1% to 0.5% of the powder mass is added. The dispersant is selected from one or more of polyethylene glycol, sodium hexametaphosphate, or sodium tripolyphosphate.

8. The method according to claim 1, characterized in that, In step (1), a grinding aid of 0.1% to 0.5% of the sawdust mass is added during the grinding process. The grinding aid is selected from one or more of triethanolamine, ethylene glycol, and sodium polyacrylate.

9. The method according to claim 1, characterized in that, The functional compounding in step (4) is as follows: the modified functional filler obtained after graded surface modification treatment is compounded and mixed with functional additives at a mass ratio of 100:0.2~2. The functional additives are selected from one or more of antioxidants, light stabilizers, flame retardants and antistatic agents.

10. The application of a sawdust-based functional filler prepared by the method according to any one of claims 1 to 9, characterized in that: The coarse-grained modified component is used as an extender filler in plastic and rubber products; the medium-grained modified component is used as an extender filler in coatings and adhesives; and the ultrafine silica powder modified component is used as a reinforcing filler in high-performance plastics and functional coatings.

Citation Information

Patent Citations

  • Fluidized bed technology for processing and separating ultrafine silicon dioxide micropowder from stone processing sawn mud

    CN104386701A

  • Comprehensive utilization method of granite type stone slab sawing mud tailings containing iron, feldspar, quartz and like

    CN112844814A